The effects of acute exercise and exercise training on plasma homocysteine: A meta-analysis - Deminice, R.; Farias Ribeiro, D.; Trevisan Frajacomo, F. T. (PLOS ONE, 2016)
Although studies have demonstrated that physical exercise alters homocysteine levels in the blood, meta-analyses of the effects of acute exercise and exercise training on homocysteine blood concentration have not been performed, especially regarding the duration and intensity of exercise, which could affect homocysteine levels differently. Objective: The aim of this meta-analysis was to ascertain the effects of acute exercise and exercise training on homocysteine levels in the blood. Method: A review was conducted according to the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses using the online databases PubMed, SPORTDiscus, and SciELO to identify relevant studies published through June 2015. Review Manager was used to calculate the effect size of acute exercise and exercise training using the change in Hcy plasmaserum concentration from baseline to post-acute exercise and trained vs. sedentary control groups, respectively. Weighted mean differences were calculated using random effect models. Results: Given the abundance of studies, acute exercise trials were divided into two subgroups according to exercise volume and intensity, whereas the effects of exercise training were analyzed together. Overall, 22 studies with a total of 520 participants indicated increased plasma homocysteine concentration after acute exercise (1.18 µmol/L, 95% CI: 0.71 to 1.65, p < .01). Results of a subgroup analysis indicated that either long-term exercise of low-to-moderate intensity (1.39 µmol/L, 95% CI: 0.9 to 1.89, p < .01) or short-term exercise of high intensity (0.83 µmol/L, 95% CI: 0.19 to 1.40, p < .01) elevated homocysteine levels in the blood. Increased homocysteine induced by exercise was significantly associated with volume of exercise, but not intensity. By contrast, resistance training reduced plasma homocysteine concentration (-1.53 µmol/L, 95% CI: -2.77 to -0.28, p = .02), though aerobic training did not. The cumulative results of the seven studies with a total of 230 participants in exercise training analysis did not demonstrate a significant impact on homocysteine levels in the blood (-0.56 µmol/L, 95% CI: -1.61 to 0.50, p = .23). Conclusions: Current evidence demonstrates that acute exercise increases homocysteine levels in the blood independent of exercise duration and intensity. Resistance, but not aerobic training decreases plasma homocysteine levels.